A decision support system for type 1 diabetes mellitus diagnostics based on dual channel analysis of red blood cell membrane fluidity. (August 2018) - Cordelli, Ermanno; Maulucci, Giuseppe; De Spirito, Marco; Rizzi, Alessandro; Pitocco, Dario; Soda, Paolo
Highlights: Investigate the use of human cells membrane fluidity for type 1 diabetes monitoring. We present a decision support system that classifies type 1 diabetes mellitus patients. The experiments were carried out on a wide dataset of images from the subjects. The results outperform the glycosylated hemoglobin test used in the state-of-the-art. Abstract: Background and objective: Investigation of membrane fluidity by metabolic functional imaging opens up a new and important area of translational research in type 1 diabetes mellitus, being a useful and sensitive biomarker for disease monitoring and treatment. We investigate here how data on membrane fluidity can be used for diabetes monitoring. Methods: We present a decision support system that distinguishes between healthy subjects, type 1 diabetes mellitus patients, and type 1 diabetes mellitus patients with complications. It leverages on dual channel data computed from the physical state of human red blood cells membranes by means of features based on first- and second-order statistical measures as well as on rotation invariant co-occurrence local binary patterns. The experiments were carried out on a dataset of more than 1000 images belonging to 27 subjects. Results: Our method shows a global accuracy of 100%, outperforming also the state-of-the-art approach based on the glycosylated hemoglobin. Conclusions: The proposed recognition approach permits to achieve promising results.